تأثیر مخارج دولت با تأکید بر بودجه عادی و انکشافی بر شاخص توسعۀ انسانی در اقتصاد افغانستان - Behzad Rahimi, Parwiz; Noori, Ahmad Zia; Hemmati, Mohammad Rasool (Farah Research and Scientific Journal, 2025)
Today, the government's role in human development is very important, so that this sector can greatly affect the human development path of countries and change people's lives. The importance of human development for the development of societies has caused international organizations and countries of the world to pay a lot of attention to this issue, so that the United Nations determines the human development status of the countries of the world annually by measuring the human development index. Although many researches in different countries have investigated this issue, none of these researches have investigated the effect of government expenditures on the human development index for Afghanistan with this method of research. Therefore, the purpose of this research is to examine the effect of government expenditures with emphasis on the common and development budget on the human development index during the period of 2003 to 2023 with the autoregressive approach with distributional breaks (ARDL). The results of the research indicate that on the one hand there is a significant positive relationship between the government's common expenditures and the human development index, that is, the increase in current government expenditures has increased the human development index through changes in the three components of this index, but development expenditures statistically does not show a significant relationship with the human development index in the country. On the other hand, the results of the research show a positive and significant relationship between the government's general expenditures (sum of common and developmental expenditures) and the human development index in the country.